Perceived Effectiveness of Dairy Service Delivery Systems in Namakkal District of Tamil Nadu (Indian Journal of Extension Education, 2019)
The present study was conducted in Namakkal District of Tamil Nadu to analyse the perceived effectiveness of various dairy service delivery systems like dairy co-operative, private integrators, public departments, private veterinarians, para-veterinarians, etc. and their extent of share in delivering the dairy services to farmers. A total of 120 respondents were selected for the study by proportionate random sampling method and the data were collected by personal interview method using pre-tested interview schedule. Most of the respondents predominantly availed the curative (99.17%) and preventive (95.00%) services from the private veterinarians; and medicines from the pharmacies (98.33%) than other dairy service delivery systems. The para-veterinarians are the major source for 75.83 per cent of the respondents for availing artificial insemination services. The respondents predominantly availed the services like concentrate feed (73.33%); mineral mixture (73.33%); insurance (57.78%) and training and advisory services (60.00%) from dairy co-operative, whereas fodder seeds & slips and credit facilities were mainly availed from neighbours (59.17%) and banks (12.50%) respectively. Overall it was perceived that the public department was effective in delivering heath and artificial insemination services, providing insurance and mineral mixture to the dairy farmers while the dairy co-operative was perceived to be effective in supplying fodder seeds and slips, credit facilities and training and advisory services. The commercial feed agencies were perceived as the effective service provider in supplying commercial concentrate feed than others.